The Epidemiology of Human Immunodeficiency Virus (HIV) and Syphilis in Ghana: A Five-Year Single Urban Site Parallel Population-Based Analysis vis-à-vis the Sentinel Survey - James Osei-Yeboah; Sylvester Yao Lokpo; Francis Abeku Ussher; Verner Ndudiri Orish; Abdul-Wahab Mawuko Hamid; Mavis Puopelle Dakorah; Tibemponi Ntoni; Emmanuel Agbeko Nani; Felix Ayroe; Daniel Adigbli (Journal of Tropical Medicine)
The study was aimed at comparing the estimation of the burden and trends (2012–2016) of Human Immunodeficiency Virus (HIV) and Syphilis infections by the national Sentinel Survey vis-à-vis the use of population-based studies at a single urban site (Municipal Hospital) in Ho, the Volta Region of Ghana. Using blood donors as a proxy of the asymptomatic adult population, a retrospective analysis of secondary data on HIV and Syphilis testing was conducted using Ho Municipal Hospital’s archives comprising 4,180 prospective blood donors. Published reports from the National Sentinel Survey for the Ho Sentinel Site comprising 2,452 pregnant women from 2012 to 2016 were used. The cumulative prevalence of HIV and Syphilis infections in the population-based survey was 4.78% and 2.58% while the epidemiology was estimated at 2.75% and 0.24% by the Sentinel Survey for the five-year under review. The new HIV and Syphilis infections were 3.78% and 2.46% in the population-based survey compared to 2.64% and 0.23% in the Sentinel Survey. Gender cumulative prevalence and the yearly trend was found to be higher in the general population compared to the pregnant women. The use of pregnant women to estimate the HIV and Syphilis epidemiology might not be representative of the general population.